Implementation Of New Public Service In Policing: The Role Of Citizen Police Academies - Murat Ozkan (European Scientific Journal, ESJ, 2016)
The New Public Service encourages involving citizens in decisionmaking process of governing. Community policing approach relies on active community relations and input. Citizen Police Academies (CPA’s) served both purposes. This study discusses the tenets of the New Public Service and evaluates CPA’s impact on citizen satisfaction and attitude toward police. It presents CPA’s and similar programs as an effective tool to increase police citizen interaction and to gain community support.